Cannabis Use Is Associated with Pain Severity and Interference Among Cancer Survivors - Shannon Nugent; Emile Latour; Jeong Lim; Jackilen Shannon; Benjamin J. Morasco (Integrative Medicine Reports)
Context: Cannabis use for symptom management among individuals with cancer is increasingly common. Objectives: We sought to describe the (1) prevalence and characteristics of cannabis use, (2) perceived therapeutic benefits of cannabis use, and (3) examine how use of cannabis was associated with self-reported pain, mood, and general health outcomes in a representative sample of patients treated at a National Cancer Institute (NCI)-designated Oregon Health and Science University Knight Cancer Institute. Methods: We conducted a population-based, cross-sectional survey developed in conjunction with 11 other NCI-designated cancer centers and distributed to eligible individuals. The survey inquired about characteristics of cannabis use, perception of therapeutic benefits, pain, mood, and general health. Responses were population weighted. We examined the association of cannabis use with self-reported pain, mood, and general health using logistic regression controlling for relevant sociodemographic and clinical characteristics. Results: A total of 523 individuals were included in our analytic sample. A total of 54% endorsed using cannabis at any time since their cancer diagnosis and 42% endorsed using cannabis during active treatment. The most commonly endorsed reasons for use included the following: sleep disturbance (54.7%), pain (47.1%), and mood (42.6%). We found that moderate pain was associated with more than a twofold (odds ratio = 2.4 [95% confidence interval = 1.3–4.6], p = 0.002) greater likelihood of self-reported cannabis use. Depressed mood and general health were not associated with cannabis use. Conclusions: In a state that had early adoption of medical and recreational cannabis legislation, a high number of cancer survivors report cannabis use. Moderate or more severe pain was associated with an increased likelihood to use cannabis, while mood and general health were not associated. Oncologists should be aware of these trends and assess use of cannabis when managing long-term symptoms of cancer and its treatments.